'The Congo must have a presence on Belgian soil.' The concept of representation in governmental discourses on the architecture of the Ministry of Colonies in Brussels, 1908–1960. Issue 7 (3rd October 2017) - van de Maele, Jens; Lagae, Johan
Abstract : While parliament buildings and governor's palaces have been studied as embodiments of governmental or colonial power, the architecture of the often more mundane state administrative office buildings has only received scant attention from architectural historians. In this article, we seek to demonstrate that political discourses concerning such buildings can nonetheless reveal important conceptions of colonial power. Rather than focussing on how such power was accommodated in and shaped by state-built architecture overseas, this article draws attention to the representational aspects of colonial governance in a mother country through an analysis of various projects proposed for the Belgian Ministry of Colonies (1908–1960). In the 1930s, when it was still housed in an eighteenth-century neoclassical building in Brussels, the Ministry of Colonies was included in a visionary but unsuccessful civil service reform, which was aimed at a modernisation of the Belgian state bureaucracy and its office buildings. After the Second World War, when colonialism became increasingly criticised in international fora, successive Belgian Ministers of Colonies pleaded for the construction of a new, grandiose ministerial complex, which was supposed to symbolise efficiency, modernity, and—above all —the permanence of the colonial undertaking. Even though important steps were taken to realise this complex, the project was outrun by the global decolonisation process, of which the independence of the Belgian Congo (1960) was an inevitable outcome.